THE INFLUENCE OF DIETARY AND LIFESTYLE FACTORS ON PSORIASIS - Rzadkowolska, Katarzyna; Żebrowska, Agnieszka (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2019)
Psoriasis is a chronic, inflammatory skin disease. It includes many forms that differ from each other in the clinical picture. In the pathogenesis of psoriasis and in exacerbations of symptoms, environmental factors are important. There are individual reports that the symptoms of psoriasis may increaseas a result of increased gluten supply in the patient’s diet. Data concerning the coexistence of this dermatosis with hypersensitivity to gluten (although it is stillinc onclusive) suggests that this factor may affect the course of the disease. Researches also indicate a relationship between psoriasis and the occurrence of obesity. Furthermore, attention is drawn to the fact that a properly composed diet enables regulation of inflammatory mechanisms that are extremely important in this disease. Numerous studies also confirm more frequent occurrence of tobacco and alcohol addiction among patients with psoriasis.